Enhancement of Critical Current Density in the (YBa2Cu3O7-/Y2O3)  N Multilayered Films - Duc, Tran Hai; Nhan, Duong Thi Thanh; Sinh, Nguyen Huy (VNU Journal of Science: Mathematics - Physics; Vol 30 No 3, 2014)
Abstract: The enhancement of critical current density ( J c ) in the (YBa 2 Cu 3 O 7- d (YBCO)/Y 2 O 3 ) ´ N multilayered films was reported. The (YBCO/Y 2 O 3 ) ´ N multilayered films in which N was varied from 0 to 10 were prepared by using the pulsed laser deposition (PLD) technique. Magnetization data measured at 65 K showed that J c of the (YBCO/Y 2 O 3 ) ´ N multilayered films was enhanced in comparison with that of the pure YBCO film. More interestingly, the J c enhancement was obtained to increase at small values of N, reach the maximum at N = 5, then decrease with increasing N to 10. The J c enhancements in the (YBCO/Y 2 O 3 ) ´ N multilayered films with N £ 5 were attributed to the increases in the number of single YBCO layers. The microstructure degradation in the (YBCO/Y 2 O 3 ) ´ N multilayered films with N > 5 was likely to be reason for the decreases in their J c , which was confirmed by using the scanning electron microscopy (SEM) images.  Keywords: YBCO, critical current density J c , multilayered films.